2020
DOI: 10.1177/0885328219899238
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo biocompatibility of novel tannic acid-collagen type I injectable bead scaffold material for breast reconstruction post-lumpectomy

Abstract: Breast cancer is the most common invasive cancer in women worldwide. Surgical removal of the breast tumor and subsequent reconstructive surgery can result in complications such as infection or necrosis of transplanted adipose tissue. Breast cancer recurrence is also a serious concern for patients. Our group has developed a tannic acid/collagen bead material that has the potential to be used as an injectable adipose tissue regenerative device to replace lipofilling. Tannic acid is a polyphenol with anticancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
(111 reference statements)
0
16
0
Order By: Relevance
“…After injection, no symptoms of reactions from the immunological system were noticed. After 3 months, the implant showed incorporation into the native tissue, and fat cell growth was observed [108]. It was demonstrated that collagen-tannic acid complexes have good biocompatibility and bioactivity as they stimulate cell proliferation [109].…”
Section: Collagen-tannic Acidmentioning
confidence: 99%
“…After injection, no symptoms of reactions from the immunological system were noticed. After 3 months, the implant showed incorporation into the native tissue, and fat cell growth was observed [108]. It was demonstrated that collagen-tannic acid complexes have good biocompatibility and bioactivity as they stimulate cell proliferation [109].…”
Section: Collagen-tannic Acidmentioning
confidence: 99%
“…17,22,23,33,34 Our laboratory has developed a dual tissue regenerative and breast cancer recurrence preventative bead material by incorporating TA into a porous collagen bead scaffold seeded with patient derived preadipocytes. 17,19,23 The goal of these collagen/TA beads are to act as a minimally invasive injectable implant for breast reconstruction post lumpectomy. The cells and porous collagen form the foundation to regenerate healthy fatty breast tissue within surgical voids.…”
Section: Discussionmentioning
confidence: 99%
“…17,22,23,27 Previous research has established the biocompatibility of beads in vivo and its efficacy in inducing selective apoptosis in breast cancer cell lines. 17,19,23 This research seeks to reliably control the bead diameter and the quantity of donor cells seeded onto the beads, which are both essential for bead material performance in vivo. As a tissue regenerative scaffold, collagen/TA beads seeded with actively proliferating cells are key to generating healthy loose connective tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations